Time Series Analysis Indicators under Directional Changes: The Case of Saudi Stock Market - Monira Essa Aloud (International Journal of Economics and Financial Issues, 2016)
We introduce a set of time series analysis indicators under an event based framework of directional changes (DC) and overshoots. Our aim is to map continuous financial market price data into the so-called DC Framework - A state based discretization of basically dissected price time series. The DC framework analysis relied on understanding the price time series as an event-based process, as an alternative of focusing on their stochastic character. Defining a scheme for state reduction of DC Framework, we show that it has a dependable hierarchical structure that permits for analysis of financial data. We show empirical examples within the Saudi Stock Market. The new DC indicators represent the foundation of a completely new generation of financial tools for studying volatility, risk measurement, and building advanced forecasting and automated trading models.